2009 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--4811
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing High School Students’ Career Considerations In Stem Fields

Abstract: His career experiences include industrial consulting and managing an outreach center. Dr. David Batts received his BS degree in Industrial Technology, MS degree in Occupational Safety and EdD in Educational Leadership from East Carolina University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…This result concurs with that of Halim et al (2018) who found that social media and familiarities are the primary elements that have a significant impact on students' decisions to pursue STEM careers. Intrapersonal factors also influence undergraduates' choice of STEM fields and in agreement with the study of Kauffmann et al (2009) who found that intrapersonal factors have the biggest impact on high school students' choice of careers in STEM disciplines. Furthermore, career outcomes expectancy influence undergraduates' choice of STEM fields as corroborated by Miller and Hurlock (2017) whose finding revealed that career outcome expectancy highly influence STEM-promising females' decision to attend a non-research-intensive undergraduate institution.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This result concurs with that of Halim et al (2018) who found that social media and familiarities are the primary elements that have a significant impact on students' decisions to pursue STEM careers. Intrapersonal factors also influence undergraduates' choice of STEM fields and in agreement with the study of Kauffmann et al (2009) who found that intrapersonal factors have the biggest impact on high school students' choice of careers in STEM disciplines. Furthermore, career outcomes expectancy influence undergraduates' choice of STEM fields as corroborated by Miller and Hurlock (2017) whose finding revealed that career outcome expectancy highly influence STEM-promising females' decision to attend a non-research-intensive undergraduate institution.…”
Section: Discussionsupporting
confidence: 87%
“…Graduates in the fields of STEM are developing solutions targeted at solving the present-day problems, yet more are in demand over the past few decades (Abe & Chikoko, 2020;Compeau, 2016). Despite growing demand of expertise, research have reported inadequacy in the number of students willing to take up careers in STEM disciplines despite high demand (Byars-Winston et al, 2010;Crisp et al, 2009;Kauffmann et al, 2009). While there are global, national and domestic efforts to encourage students to study STEM related disciplines for over three decades, the projection in terms of expertise have been well speculated and funded to propel emerging learners (Litchtenberger & Casey, 2018;National Science Board, 2017;OECD, 2019b;Peña-Calvo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, the school type and classroom activities (environmental factor) also tend to impact students' STEM interests and career aspirations. School environment and curriculum that actively supports formal and informal scientific investigations aid in nurturing STEM interests and career aspirations [3,21,31,33,34]. A longitudinal study by Ketenci et al [35], has shown variability in STEM aspirations in public and private schools [35].…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…Research conducted within this area has identified numerous factors reported by students to have influenced the choice to pursue engineering as a college major. These factors include math-and science-related interest [1][2], prior STEM experiences in elementary and secondary school [3], earning potential [1,[4][5], and positive self-assessment of one's math, science, and/or problem-solving skills [2,[6][7]. Social relationships such as those of family [8][9][10][11], peers, and teachers have also been cited by students as key factors influencing their choice to pursue engineering [12].…”
Section: Introductionmentioning
confidence: 99%